ANALISIS IMPLEMENTASI PERJANJIAN PEMBIAYAAN DENGAN JAMINAN FIDUSIA PADA PT. ASTRA CREDIT COMPANIES SURABAYA - Talitha Nabilah; Mas Anienda Tien F (Gapenas Publisher, 2023)
This study aims to determine and analyze the implementation of financing agreements with fiduciary guarantees at PT. Astra Credit Companies Surabaya and know and analyze efforts to resolve defaults at PT. Astra Credit Companies Surabaya. This type of research uses a type of empirical juridical research with data sources obtained directly from the community. The source of data in this study is using primary data and secondary data. This research data collection method was obtained through literature / document studies, literature, scientific papers, applicable legislation, and interviews from several related sources. The results of this study can be concluded that in the implementation of financing agreements with fiduciary guarantees at PT. Astra Credit Companies Surabaya still has discrepancies. With this discrepancy, PT. Astra Credit Companies Surabaya makes efforts to resolve this financing agreement against defaults committed by debtors, either by giving warnings or through litigation.